Minat Mengkuti Pendidikan Profesi Akuntansi (PPAK) Pada Mahasiswa Universitas Udayana - Dewi Sukmawati, Ni Made; Asri Dwija Putri, I Gusti Ayu Made (E-Jurnal Akuntansi; Vol 33 No 7 (2023)DO - 10.24843/EJA.2023.v33.i07.p14, 2023)
The aim of the study was to look for the factors that influence the interest in taking part in the Accounting Profession Education (PPAk) for Udayana University students. The population of this study were all regular and non-regular accounting students at the Faculty of Economics and Business, Udayana University. The research sample was taken using the slovin formula, so that a total sample of 67 students was obtained. Collecting research data using questionnaires and data analysis techniques used multiple linear regression. The results of the analysis show that economic motivation, career motivation, educational costs and parental support have a positive effect on students' interest in participating in PPAk. Meanwhile, degree motivation has no effect on students' interest in taking PPAk. Keywords: Economic motivation; degree motivation; career motivation; education costs; parental support, interest in attending Education